(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2015)
The article deals with philosopher Günther Stern Anders’s response to the airing of the NBC miniseries Holocaust in Austria and in Western Germany in 1979. While much has been written about the TV miniseries, the reaction of Anders (1902–1992) has not been the object of discussion. The present article first examines the debate on the witnessing, visualization and representation of the Shoah (Adorno, Agamben, Didi-Huberman, Lanzmann and Levi), focusing in particular on the American TV miniseries Holocaust, and then investigates Günther Anders’s reaction to this controversial fiction in the essay ‘Nach “Holocaust”’ (1979). Anders’s remarks about the miniseries are important in connection with his cultural-philosophical studies on Auschwitz and Hiroshima- Nagasaki as major turning points, as well as his theory of media. It is remarkable that Anders was one of the first intellectuals to develop an interest in television as a new medium.